Effectiveness of Audiovisual Distraction Techniques on Reducing Hospitalized Anxiety in Preschool Children : A Case Study - Merlina Retnosari; Irdawati (GLOBAL HEALTH SCIENCE GROUP, 2026)
Hospitalization anxiety is a psychological response often experienced by preschool-aged children due to medical procedures that cause fear and discomfort. Untreated anxiety can lead to uncooperative behavior and hinder the treatment process. One non-pharmacological nursing intervention that can be used is audiovisual distraction techniques. This study aims to determine the effectiveness of audiovisual distraction techniques in reducing hospitalization anxiety in preschool-aged children. This study used a case study design with a pre-post test approach. The study subjects were 10 preschool-aged children undergoing medical procedures at RSDM. The intervention, in the form of audiovisual distraction by watching cartoons, was given during the nursing procedure. Anxiety levels were measured using the Face Anxiety Scale (FAS) before and after the intervention. The results showed a decrease in anxiety scores in all subjects, from moderate to very anxious to mild anxiety or even no anxiety after the intervention. Audiovisual distraction techniques have been proven effective in reducing hospitalization anxiety levels in preschool-aged children.